IMPACT OF CURRENT DIET AT THE RISK OF NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD) - DUARTE,Sebastião Mauro Bezerra (2019)
ABSTRACT The nonalcoholic fatty liver disease (NAFLD) affects approximately 20%-30% of general population and is even more prevalent among obese individuals. The risk factors mainly associated with NAFLD are diseases related to the metabolic syndrome, genetics and environment. In this review, we provide a literature compilation evaluating the evidence behind dietary components, including calories intake, fat, protein, fibers and carbohydrate, especially fructose which could be a trigger to development and progression of the NAFLD. In fact, it has been demonstrated that diet is an important factor for the development of NAFLD and its association is complex and extends beyond total energy intake.